An injectable PEG-based hydrogel synthesized by strain-promoted alkyne–azide cycloaddition for use as an embolic agent. Issue 4 (4th January 2016) - Su, Xin; Bu, Linlin; Dong, Hui; Fu, Shuangli; Zhuo, Renxi; Zhong, Zhenlin
Abstract : Cyclooctyne and azide functionalized PEGs are prepared by ring-opening polymerization. They form a biodegradable hydrogel in situ to temporarily block rabbit ear vessels. Abstract : With PEG as a macromolecular initiator, cyclooctyne and azide functionalized PEGs were conveniently prepared by the ring-opening polymerization of cyclooctyne-bearing epoxy monomer and azide-bearing cyclocarbonate monomer, respectively. Via the strain-promoted alkyne–azide cycloaddition (SPAAC) reaction of cyclooctyne and azide groups, the two PEG polymers formed a hydrogel in a few minutes upon simply mixing under physiological conditions. The formation, degradation, and biocompatibility of the hydrogel were investigated in vitro and in vivo . Injection of a mixture of the gel precursors into the auricular central artery of rabbits blocked the fast-flow of the vessel rapidly without any invasive operation, and the vessel flow restored spontaneously by gel degradation in two days. This kind of injectable hydrogel would be useful for staunching wounds and blocking blood vessels temporarily.